APLIKASI TEKNIK STATISTIKA NONPARAMETRIK UNTUK DATA NOMINAL (Studi Kasus: Variabel yang mempengaruhi biaya langsung konstruksi bangunan gedung) - Mangitung, Donny M. (MEKTEK, 2007)
Spearman rho correlation and chi square cross tabulation techniques were employed to analyse secondary data with regards to a case study of direct cost for building constructions in 7 (seven) regencies/city in the Nanggroe Aceh Darussalam (NAD). The first technique was used to test statistically the rank differences of variables influencing direct costs among the seven regencies/city, while the second was employed to know the differences of frequencies of contractors’ perception regarding such direct cost from 7 (seven) regencies/city. The result shows that the ranks of direct cost variables from the highest to the lowest (i.e. material cost, transportation cost of materials, equipment rental cost, equipment operational cost, worker skills related costs, basic wages, wages related to location, wages related to work types) are significantly correlated between 7 (seven) regencies/city in NAD including significant correlation to the sum of 7 (seven) regencies/city. In spite of that, there are four variables influencing direct cost showing the differences of frequencies from 7 (seven) regencies/city in NAD, namely, transportation cost of materials, equipment rental cost, wages related to work types and wages related to location condition. While material cost, equipment operational cost, basic wages, worker skills related costs show no differences.